Soil conservation effectiveness and crop productivity of forage legume intercropping, contour grass barriers and contour ridging in cassava on Andean hillsides - Leihner, D.E.; Ruppenthal, M; Hilger, TH; Castillo Franco, J.A. (Cambridge University Press, 1996)
Soil erosion and the productivity of cassava (Manihot esculenta Crantz) cropping systems, including forage legume intercropping, were monitored under natural rainfall conditions on Inceptisols in southwest Colombia. Trials were conducted over two cropping periods on moderate slopes. The best erosion control and cassava fresh root yields were achieved by sole cropping on contour ridges. Erosion was greater with forage legume intercropping than with cassava sole cropping in the first cropping period but once well established and uniformly distributed, undersown legumes controlled erosion effectively, though yields of cassava were depressed by 40% or more. Dense stands of grass contour barriers decreased erosion to tolerable levels. Lower cassava yields due to reduced cropping area and competition from the grasses could be compensated for by the production of valuable forage and by increasing cassava planting density.